Gap Implementation of Thematic Tourism Development Policy in Kampung Sayur Banjarbaru City - Dewi Purboningsih; Trisylvana Azwari; Nana Abdul Aziz (Jurnal Public Policy, 2023)
Banjarbaru city government's efforts to improve the development of tourist destinations by enacting Banjarbaru City Regional Regulation Number 3 of 2019 concerning the 2019-2034 Regional Tourism Development Master Plan. However, the implementation of the tourist destination development plan has not been fully achieved. The existence of gaps or gaps in the implementation of the development of tourist destinations, especially Kampung Sayur  tourism in Banjarbaru City, is influenced by resource factors which include human resources and facility resources, so the needs of tourist destinations have not been fulfilled. Namely attractions, accessibility, facilities and additional services. This study aims to determine the gaps in policy implementation in the development of Kampung Sayur thematic tourism in Banjarbaru City. This research method uses a qualitative approach. The collection technique was carried out through observation in Kampung Sayur and interviews with several informants, including: (1) employees of the Department of Youth, Sports, Culture and Tourism of Banjarbaru City; (2) the Head of Agriculture and Plantation Service of Central Ulin Village. The results of the study stated that the development of Kampung Sayur tourism in the North Ulin District had not been carried out. This is influenced by several inhibiting factors, including the absence of Kampung Sayur tourism center, the absence of vacant land owned by the government village for infrastructure development as a means of supporting tourists, the absence of public transportation access, and the absence of Tourism Awareness Group (POKDARWIS).